2016
DOI: 10.3892/etm.2016.3053
|View full text |Cite
|
Sign up to set email alerts
|

Addition of fentanyl to the ultrasound-guided transversus abdominis plane block does not improve analgesia following cesarean delivery

Abstract: Abstract. The present study aimed to investigate whether the addition of fentanyl to the transversus abdominis plane (TAP) block procedure may improve analgesic duration following cesarean delivery. A total of 147 nulliparous women with an American Society of Anesthesiologists physical status I-II, scheduled for elective cesarean delivery under spinal anesthesia, were enrolled in the present study. All patients underwent cesarean delivery under spinal anesthesia with 10 mg bupivacaine and 10 µg fentanyl, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In Wang LZ et al study, when Fentanyl was added to ropivacaine in ultrasound guided TAP block for caesarean section under subarachnoid block, there was no improvement in postoperative pain outcome and no significant differences in the postoperative nausea and vomiting sedation levels. 7 In our study, the sedation scores were higher in group BF compared to Group B at 0-hour, 2hour, 4-hour, 6-hour, 12-hour and 24-hour. The difference in Sedation scores, between Group BF and Group B was statistically significant at 4-hour (p= 0.01 < 0.05).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…In Wang LZ et al study, when Fentanyl was added to ropivacaine in ultrasound guided TAP block for caesarean section under subarachnoid block, there was no improvement in postoperative pain outcome and no significant differences in the postoperative nausea and vomiting sedation levels. 7 In our study, the sedation scores were higher in group BF compared to Group B at 0-hour, 2hour, 4-hour, 6-hour, 12-hour and 24-hour. The difference in Sedation scores, between Group BF and Group B was statistically significant at 4-hour (p= 0.01 < 0.05).…”
Section: Discussionsupporting
confidence: 42%
“…Many adjuvants including fentanyl have been studied for local anaesthetics to extend the duration of postoperative analgesia following regional blocks. 7 Aims and Objectives The current study was done to evaluate as to whether Fentanyl as an adjuvant to local anaesthetic bupivacaine improves the quality and duration postoperative analgesia of transversus abdominis plane block in abdominal hysterectomy.…”
mentioning
confidence: 99%
“…Addition of fentanyl to ropivacaine for TAP block after cesarean section in one study did not show any effect on mean time to first use of PCA, overall use of PCA, or in postoperative VAS scores when compared to use of ropivacaine alone. 13 Combination of dexamethasone to ropivacaine (Dex-R) for TAP blocks has also yielded inconsistent results in different studies. In one study, TAP block after inguinal hernia repair with Dex-R was associated with lower pain score at 24 hours postop and lower morphine use in the first 24 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[1819202122232425262728293031] Most of the investigators used ultrasound-guided TAP block; only in two studies TAP block was performed by anatomical landmark technique. [2021]…”
Section: Regional Nerve Infiltration Technique: Transversus Abdominismentioning
confidence: 99%
“…These included adding clonidine or fentanyl and increasing the dose of LA, but all of them failed to show any benefit. [242730] When TAP block was compared as a part of multimodal analgesia comprising epidural morphine, less consumption of patient-controlled analgesia (PCA) morphine was noted. [28] In two other studies, TAP block was observed to be equally effective in comparison to wound infiltration for analgesia.…”
Section: Regional Nerve Infiltration Technique: Transversus Abdominismentioning
confidence: 99%